Pete the Cat's wacky taco Tuesday - Dean, Kim 1969; Dean, James 1957 (New York, N.Y. HarperFestival, 2024)
Pete the Cat and his family are making tacos in this storybook by New York Times bestselling author-illustrator team Kimberly and James Dean. Includes over thirty stickers!
Inclusion of accompanying material (stickers) may vary by owning library.
113408
Keywords: Pete -- the Cat (Fictitious character) -- Juvenile fiction; Cats -- Juvenile fiction; Tacos -- Juvenile fiction; Humorous fiction; Picture books